Antioxidant Activity of Resveratrol Diastereomeric Forms Assayed in Fluorescent-Engineered Human Keratinocytes - Ilaria Bononi; Paola Tedeschi; Vanessa Mantovani; Annalisa Maietti; Elisa Mazzoni; Cecilia Pancaldi; Vincenzo Brandolini; Mauro Tognon (MDPI AG, 2022)
Resveratrol is a powerful antioxidant molecule. In the human diet, its most important source is in Vitis vinifera grape peel and leaves. Resveratrol exists in two isoforms, cis- and trans. The diastereomeric forms of many drugs have been reported as affecting their activity. The aim of this study was to set up a cellular model to investigate how far resveratrol could counteract cytotoxicity in an oxidant agent. For this purpose, a keratinocyte cell line, which was genetically engineered with jelly fish green fluorescent protein, was treated with the free radical promoter Cumene hydroperoxide. The antioxidant activity of the trans-resveratrol and its diastereomeric mixture was evaluated indirectly in these treated fluorescent-engineered keratinocytes by analyzing the cell number and cell proliferation index. Our results demonstrate that cells, which were pre-incubated with resveratrol, reverted the oxidative damage progression induced by this free radical agent. In conclusion, fluorescent-engineered human keratinocytes represent a rapid and low-cost cellular model to determine cell numbers by studying emitted fluorescence. Comparative studies carried out with fluorescent keratinocytes indicate that trans-resveratrol is more efficient than diastereomeric mixtures in protecting cells from the oxidative stress.